Risk and resilience factors for primary school dropout in Côte d’Ivoire - Wortsman,. Brooke; Capani, Angela; Brice, Henry; Ball, Mary-Claire; Zinszer, Benjamin; Tanoh, Fabrice; Akpe, Yapo, Hermann; Ogan, Amy; Wolf, Sharon; Jasińska, Kaja (My University, 2022)
We examined child-, family-, and school-level risk and resilience factors associated with dropout using longitudinal data of fifth-grade students in rural Côte d’Ivoire (N=1195, Mage=10.75, SDage=1.42). Children who dropped out were older, involved in more child labour, had poorer literacy, owned fewer books, and attended schools with poorer learning environments. Cumulative risk (CR) indices revealed that child-level CR most strongly predicted dropout (b=-0.86, OR=0.42); further, children with low child-level CR were more likely to drop out when family-level CR was high (b=0.23, OR=1.25). Better school infrastructure and teachers were protective for children who were at high risk of dropout yet remained enrolled. Although child- and family-level factors contribute to risk of dropout, school-level factors may mitigate risks and promote academic resilience amongst students in West Africa.
Supplemental Materials: https://osf.io/5yubf/
Keywords: Côte d’Ivoire; ecological systems; educational risk and resilience; Primary school dropout; sub-Saharan Africa